Uarda : a Romance of Ancient Egypt $1 (BCompletes - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"Uarda: a Romance of Ancient Egypt $1 (BComplete" by Georg Ebers is a historical novel likely written in the late 19th century. Set against the backdrop of ancient Egypt during the time of the Pharaohs, the narrative intertwines romance and societal exploration, centering around characters like the princess Bent-Anat and her encounters with common people, including a girl from a lower social class who suffers an accident. The opening of the novel introduces the contrasting settings of Thebes, detailing the vibrant life on the eastern bank of the Nile and the somber atmosphere of the necropolis on the western side, where the dead are honored. As the narrative unfolds, we meet significant figures, including Bent-Anat and her retinue, who seek to address the injury caused to a girl from a lower social order. The interactions reveal themes of class distinction, human compassion, and the intertwining of the living and the dead in ancient Egyptian culture. Through these early chapters, the author sets the stage for a rich tapestry of relationships and conflicts that likely explore broader societal issues within this ancient civilization. (This is an automatically generated summary.)s
Release date is 2004-11-15
Produced by David Widger
Keywords: Egypt -- History -- To 332 B.C. -- Fiction; German fiction -- Translations into English